Alteridade, universitários imigrantes e fronteiras (in)visíveis na UFSM: um estudo em representações sociais - Vicentini, Ana Júlia (2023)
Numbers regarding migrations have been on the rise, as well as the presence of immigrants in higher education institutions. Thus, there is a need to understand issues related to immigrant university students, with emphasis on racism and xenophobia. The literature points out that there are still few studies on immigrant university students in Brazil, especially in the light of the Theory of Social Representations (TSR). From the TSR perspective, racism is a social representation, and it is expressed in different ways, both explicit and implicit, being a form of apprehension of the otherness. This research, at the master's degree level, intended to know the expressions of otherness in public university contexts from the narratives about immigrant students, observing the dynamics of recognition and acceptance of cultural and psychosocial differences. We outlined qualitative research, whose method includes the instruments: Questionnaire General Characteristics of the Participants (Q-CGP) and a semi-structured interview, in which we also used images as free association inductors’. We conducted ten interviews with UFSM employees, allocated in five Teaching Units. The qualitative analysis of the information took place through the Interpretation of Meanings Method, in the light of authors who subscribe to critical social psychology and/or TSR. Our initial assertion was that due to the xenophobic/racist/sexist Brazilian culture, the lack of knowledge and estrangement towards the different cultures of the countries where immigrant university students come from, UFSM employees have difficulties in establishing relationships with them that contribute to the acceptance of otherness. We confirmed this assertion and found that some elements of social representations about immigrant students would be linked to a stereotype of refugee, intricate, but still confused with the terms “immigrant” and “exchange student”. Another element would be the idea of disability, as the perception of a supposed inability of these students would relate to ideas of immaturity, dependence and childishness, thus awakening benevolence, a form of prejudice. We noticed the existence of racialized xenophobia at UFSM, as there are differences in attitudes and discourses in relation to refugee students compared to exchange students, but in a masked way. With an intersectional look, we found that motherhood and romantic relationships appear in the speech of the people interviewed as an additional layer of disempowerment of female immigrant students. Finally, we found that the way the institution deals with the otherness brought by immigrant and refugee students is mainly through invisibilization. This study is linked to a larger research project entitled “Sexualities, Reproductive Practices and Violence in Vir(tu)al Times in the New Brazilian Republic. Thinking about Discontens in Culture, Alterity, Affective Ties and Subjectivity”.